Lineage structure of the human antibody repertoire in response to influenza vaccination - Jiang, Ning; He, Jiankui; Weinstein, Joshua A; Penland, Lolita; Sasaki, Sanae; He, Xiao-Song; Dekker, Cornelia L; Zheng, Nai-Ying; Huang, Min; Sullivan, Meghan; Wilson, Patrick C; Greenberg, Harry B; et al. (Science translational medicine, 2013)
The human antibody repertoire is one of the most important defenses against infectious disease, and the development of vaccines has enabled the conferral of targeted protection to specific pathogens. However, there are many challenges to measuring and analyzing the immunoglobulin sequence repertoire, including that each B cell's genome encodes a distinct antibody sequence, that the antibody repertoire changes over time, and the high similarity between antibody sequences. We have addressed these challenges by using high-throughput long read sequencing to perform immunogenomic characterization of expressed human antibody repertoires in the context of influenza vaccination. Informatic analysis of 5 million antibody heavy chain sequences from healthy individuals allowed us to perform global characterizations of isotype distributions, determine the lineage structure of the repertoire, and measure age- and antigen-related mutational activity. Our analysis of the clonal structure and mutational distribution of individuals' repertoires shows that elderly subjects have a decreased number of lineages but an increased prevaccination mutation load in their repertoire and that some of these subjects have an oligoclonal character to their repertoire in which the diversity of the lineages is greatly reduced relative to younger subjects. We have thus shown that global analysis of the immune system's clonal structure provides direct insight into the effects of vaccination and provides a detailed molecular portrait of age-related effects.